State failure and state weakness in a time of terror - Rotberg, Robert I. (World Peace Foundation ; Brookings Institution Press, 2003)
A Brookings Institution Press and World Peace Foundation publication The threat of terror, which flares in Africa and Indonesia, has given the problem of failed states an unprecedented immediacy and importance. In the past, failure had a primarily humanitarian dimension, with fewer implications for peace and security. Now nation-states that fail, or may do so, pose dangers to themselves, to their neighbors, and to people around the globe: preventing their failure, and reviving those that do fail, has become a strategic as well as a moral imperative. State Failure and State Weakness in a Time of Terror develops an innovative theory of state failure that classifies and categorizes states along a continuum from weak to failed to collapsed. By understanding the mechanisms and identifying the tell-tale indicators of state failure, it is possible to develop strategies to arrest the fatal slide from weakness to collapse. This state failure paradigm is illustrated through detailed case studies of states that have failed and collapsed (the Democratic Republic of the Congo, Sierra Leone, the Sudan, Somalia), states that are dangerously weak (Colombia, Indonesia, Sri Lanka, Tajikistan), and states that are weak but safe (Fiji, Haiti, Lebanon).